Implementing a novel model for hospice and palliative care in the emergency department: An experience from a tertiary medical center in Taiwan. Issue 19 (May 2017) - Weng, Tzu-Chieh; Yang, Ya-Chun; Chen, Ping-Jen; Kuo, Wen-Fu; Wang, Wei-Lin; Ke, Ya-Ting; Hsu, Chien-Chin; Lin, Kao-Chang; Huang, Chien-Cheng; Lin, Hung-Jung
Abstract : Abstract: Hospice and palliative care has been recognized as an essential part of emergency medicine; however, there is no consensus on the optimal model for the delivery of hospice and palliative care in the emergency department (ED). Therefore, we conducted a novel implementation in a tertiary medical center in Taiwan. In the preintervention period, we recruited a specialist for hospice and palliative medicine in the ED to lead our intervention. In the early stage of the intervention, starting on July 1, 2014, we encouraged and funded ED physicians and nurses to receive training for hospice and palliative medicine and residents of emergency medicine to rotate to the hospice ward. In the late stage of the intervention, we initiated educational programs in the ED, an interdisciplinary meeting with the hospice team every month, sharing information and experience via a cell phone communication app, and setting aside an emergency hospice room for end-of-life patients. We compared the outcomes among pre-, during, and postintervention periods. Compared with 4 in the preintervention period, the cases of do not resuscitate (DNR) per month increased significantly to 30.1 in the early stage of intervention, 23.9 in late stage of intervention, and 34.6 in the postintervention period (all P  < .001 compared with the preintervention period). Compared with 10.8% in the preintervention period, the ratio of DNR orders signed in the ED/total DNR orders signed in the study hospital was increased to 17.1% in early stage of intervention, 12.5% in late stage of intervention, and 22.8% in postintervention. Compared with zero in preintervention and early intervention, the cases of consultation with the hospice team increased significantly to 19 cases per month in the late stage of intervention and postintervention. The ability of nurses in hospice and palliative care, including knowledge and the timing and method of consultation with the hospice team, was also significantly improved. We successfully implemented a novel model of hospice and palliative care in the ED via a champion, education, and close collaboration with the hospice team, which could be an important reference for other EDs and intensive care unit in the future.